"She Doesn't Have the Stamina": Hillary Clinton and the Hysteria Diagnosis in the 2016 Presidential Election. Issue 1 (2nd January 2019) - Neville-Shepard, Ryan; Nolan, Jaclyn
Abstract: Reactions to Hillary Clinton's bout with pneumonia during the 2016 presidential campaign revealed an effort to turn her health crisis into a sign of bad character, or what Johnson (2010 ) called kakoethos . We argue that the criticism of Clinton demonstrated sexist double standards related to women's health and leadership. In addition to exploring the history of candidates' health issues in presidential campaigns and describing the double standards that Clinton faced, this article explains how such discourse aimed to delegitimize Clinton while marking any female as too hysterical to lead from the White House. The article demonstrates the inherently sexist nature of kakoethos and how it activates double binds that further contain aging women leaders.